Cu single-atom nanozymes with unsaturated coordination structure drive ROS bursts to reshape the immune microenvironment for synergistic PD-1 therapy - Huimin Liu; Yuchan Xue; Shulin Shan; Fengjia Zheng; Han Ding; Yue Pan; Chunyan Ma; Yueqing Huang; Songbo Zhao (Chemical Engineering Journal, 2025)

Superior charge dynamics via ternary doping layer-by-layer strategy in high-efficiency organic solar cells - Chao Zhang; Shixiu Sun; Tengfei Han; Jie Chi; Ran Dong; Shulin Han; Hang Zhou; Yujie Xu; Lei Cai; Xiaoyan Du; Sang Young Jeong; Han Young Woo; et al. (Chemical Engineering Journal, 2025)

Crystallization-driven effect enables organic solar cells with efficiency exceeding 19.4 % - Tengfei Han; Jie Chi; Ran Dong; ShuLin Han; Hang Zhou; Yujie Xu; Byung Hui Lee; Lei Cai; Xiaoyan Du; Han Young Woo; Fujun Zhang; Chao Zhang; et al. (Chemical Engineering Journal, 2025)

Lateral dynamic response of partially embedded piles in the sea considering wave loads and wave-induced seabed dynamic response load distribution effects - Minghui Cai; Minghui Yang; Han Yang; Shulin Li (Ocean Engineering, 2025)

Revealing the degrading-possibility of methyl red by two azoreductases of Anoxybacillus sp. PDR2 based on molecular docking - Shulin Zhang; Linlin Feng; Yanyan Han; Zihang Xu; Luhui Xu; Xuejiao An; Qinghua Zhang (Chemosphere, 2024)

Integrating network pharmacology and experimental validation to explore the mechanisms of luteolin in alleviating fumonisin B1–induced intestinal inflammatory injury - Defeng Wen; Wantong Han; Quan Chen; Guanhui Qi; Mengling Gao; Pu Guo; Yu Liu; Zhongyuan Wu; Shulin Fu; Qirong Lu; Yinsheng Qiu (Toxicon, 2024)

Dominant modes and mechanisms of atmospheric rivers in East Asia - Shulin Qu; Tao Su; Zixuan Han; Bicheng Huang; Guolin Feng (Atmospheric Research, 2023)

Niche separation, dynamics, and transport pattern of trace elements along Antarctic krill (Euphausia superba) to its exclusive predator, mackerel icefish (Champsocephalus gunnari) - Shulin Han; Guoping Zhu (Marine Pollution Bulletin, 2023)

Integration of proteome and metabolome profiling to reveal heat stress response and tolerance mechanisms of Serratia sp. AXJ-M for the bioremediation of papermaking black liquor - Xuejiao An; Ningjian Li; Shulin Zhang; Yanyan Han; Qinghua Zhang (Journal of Hazardous Materials, 2023)

Effect of moisture content on the evolution of bacterial communities and organic matter degradation during bioaugmented biogas residues composting - Shulin Zhang; Bin Zhong; Xuejiao An; Yanyan Han; Xiaoshuang Xiao; Qinghua Zhang (World Journal of Microbiology and Biotechnology, 2023)

Complete mitochondrial genomes of Thyreophagus entomophagus and Acarus siro (Sarcoptiformes: Astigmatina) provide insight into mitogenome features, evolution, and phylogeny among Acaroidea mites - Yu Fang; Mingzhong Sun; Ying Fang; Zetao Zuo; Luyao Liu; Lingmiao Chu; Lan Ding; Caixiao Hu; Feiyan Li; Renrui Han; Xingquan Xia; Shulin Zhou; et al. (Experimental and Applied Acarology, 2022)

Mechanisms responsible for interdecadal variation of the thermodynamic component of East Asian summer monsoon moisture transport - Tao Su; Yue Li; Bicheng Huang; Shulin Qu; Zixuan Han; Zhonghua Qian; Guolin Feng; Yongping Wu (International Journal of Climatology, 2022)
In this study, the East Asian summer (June–July–August) monsoon (EASM) atmospheric moisture transport variability under global warming are examined using ERA‐Interim reanalysis data from 1979 to 2019. The total EASM atmospheric moisture transport is decomposed into the thermodynamic (δTH) and dynamic (δMCD) components, which are related to specific humidity and wind velocity, respectively. Based on empirical orthogonal function (EOF) analysis, both the second and the fourth modes of δTH are linked to δMCD, indicating that δMCD can impact the moisture distribution and consequently influence δTH indirectly. Both the first (δTH_EOF1) and the third (δTH_EOF3) modes of δTH show considerable interdecadal changes. It is noted that their principal components exhibit significant increasing trends in recent decades. The response of EASM moisture transport to global warming is probably reflected in these two modes. δTH_EOF1 is associated with negative phases of the Interdecadal Pacific Oscillation (IPO)/Pacific Decadal Oscillation (PDO). This causes the western North Pacific subtropical high (WNPSH) to extend westward and the strengthening of Pacific trade winds. As a result, positive precipitable water anomalies dominate East Asia and δTH_EOF1 is characterized by anomalous southwesterly moisture transport along the East China Sea to southern Japan. δTH_EOF3 corresponds to anomalous moisture transport over the Indochina Peninsula and Japan. The precipitable water associated with δTH_EOF3 in general represents a meridional dipole. Anomalous southward wind induced by the eastward extension of the WNPSH is the main reason for positive (negative) precipitable water anomalies in southern (northern) East Asian. The anomalous circulation associated with the anomalous east–west sea surface temperature gradient over the Indian Ocean affects atmospheric moisture in southern East Asian and can dramatically impact δTH_EOF3.

Genome‐wide analysis of Toll‐like receptors in zebrafish and the effect of rearing temperature on the receptors in response to stimulated pathogen infection - Hong Chen; Yue Liang; Yawen Han; Tengfei Liu; Shulin Chen (Journal of Fish Diseases, 2021)
Water temperature has a major influence on the host innate immune defence and the infectivity of pathogens in ectothermic teleosts. Toll‐like receptors (TLRs) are the first and well‐characterized innate immune receptors that are conserved in vertebrates. However, little is known about the effect of temperature variation on TLRs in fish species. In this study, we used adult zebrafish as a research model to investigate the effect of water temperature on TLRs. Whole genome searches identified 20 TLR homologue genes in zebrafish. Multiple sequence alignment and protein structure analysis revealed the conserved domains for these TLR proteins. To identify TLR genes related to temperature variation, TLR family genes from 12 species with different body temperatures were assigned to conduct phylogenetic analyses. Based on the phylogenetic relationships, TLR3 , TLR4 , TLR5 and TLR20~21 were selected as candidate genes. Immunostimulation data indicated that TLR3 , TLR5 , and TLR21 were more sensitive to temperature variation and their expression levels were affected in response to pathogen stimulation. Taken together, our results provide a new opportunity to understand the roles of temperature on host innate immune response in fishes and have broader implications for disease prevention in aquaculture.

Model test and numerical simulation on the dynamic stability of the bedding rock slope under frequent microseisms - Zhiyun Deng; Xinrong Liu; Yongquan Liu; Shulin Liu; Yafeng Han; Jinhui Liu; Yiliang Tu (Earthquake Engineering and Engineering Vibration, 2020)

Cumulative damage evolution and failure modes of the bedding rock slope under frequent microseisms - Zhiyun Deng; Xinrong Liu; Yongquan Liu; Shulin Liu; Yafeng Han; Yiliang Tu; Jun Gu (Arabian Journal of Geosciences, 2020)

HL2 on chromosome 7D of wheat (Triticum aestivum L.) regulates both head length and spikelet number - Hongni Yao; Quan Xie; Shulin Xue; Jing Luo; Jikang Lu; Zhongxin Kong; Yongpan Wang; Wenling Zhai; Nan Lu; Rong Wei; Yang Yang; Yuzhou Han; et al. (Theoretical and Applied Genetics, 2019)

Application of the SeDeM Expert System in Studies for Direct Compression Suitability on Mixture of Rhodiola Extract and an Excipient - Shulin Wan; Rui Yang; Han Zhang; Xuelian Li; Mingxian Gu; Tianbing Guan; Jianbing Ren; Huimin Sun; Chuanyun Dai (AAPS PharmSciTech, 2019)

Changes in global monsoon precipitation and the related dynamic and thermodynamic mechanisms in recent decades - Zixuan Han; Tao Su; Bicheng Huang; Taichen Feng; Shulin Qu; Guolin Feng (International Journal of Climatology, 2019)
The aim of this study is to explore the long‐term trends in the distribution of global monsoon precipitation over recent decades using the Global Precipitation Climatology Project (GPCP) data set. In addition, the potential4 mechanisms are examined by applying the atmospheric moisture budget decomposition method to the outputs from the ERA‐Interim medium‐range weather forecasting reanalysis produced by the European Centre for Medium‐Range Weather Forecasts (ECMWF). Changes in global monsoon precipitation are primarily thermodynamically caused by changes in specific humidity and dynamically caused by changes in circulation, as well as by changes in moisture transport that are driven by transient eddies and local evaporation. The results show that the increasing trends in global summer monsoon precipitation from 1979 to 2016 were dominated by contributions from the southern Asian, South African, and North American monsoon regions and were driven by the response of atmospheric circulation to the enhanced east–west thermal contrast in the tropical Pacific. We find that changes in the sea surface temperature (SST) patterns promote increased low‐level vertical velocities in monsoon regions, leading to moisture convergence through divergent circulation anomalies when combined with the climatological humidity field. Hence, the processes result in increasing trends in monsoon precipitation. In addition, evaporation makes increasing contributions to monsoon precipitation throughout the world, except in the South American monsoon region. Moreover, subtropical regions in the East Pacific (the Atlantic) may be major sources of water vapour that have supported increases in precipitation over the southern Asian and North American monsoon regions (the South African monsoon region) in recent decades.

TCR mispairing in genetically modified T cells was detected by fluorescence resonance energy transfer - Hongwei Shao; Wenfeng Zhang; Qinglian Hu; Fenglin Wu; Han Shen; Shulin Huang (Molecular Biology Reports, 2010)

Evaluation of suitable reference gene for real-time PCR in human umbilical cord mesenchymal stem cells with long-term in vitro expansion - Youwei Wang; Zhibo Han; Shulin Yan; Aibin Mao; Bin Wang; He Ren; Ying Chi; Zhongchao Han (In Vitro Cellular & Developmental Biology - Animal, 2010)